Multidisciplinary contributions to talent identification in young elite badminton players - Robertson-Martens, K. (The Japan Journal of Coaching Studies, 2021)
Badminton has been for many years known by many to be a `game` in which family members can enjoy in their backyards as a form of fun and exercise. However, it is much more than that, it is a thrilling sport that is played by millions across the world. Whilst, many people play badminton recreationally, there is a select or one might even say "privileged" group of people that get to play at the highest, most elite level. These professionals were fortunate enough to either come from countries where badminton is particularly popular, or they possess the necessary resources to invest in it.However, there also exists a large population of badminton enthusiasts who are willing to coach and play the sport at a highly competitive level but are unaware of what is required to do so. Often, in such environments, some glimmers of `talented` players are spotted, but eventually the prospects of developing them are lost. Hence the reason why, research on talent identification (TID) in badminton is needed. This research will create avenues to assist interested persons by pointing them in right direction towards the creation and development of pathways to identifying talent. Thus, this dissertation aimed at identifying what factors and components contribute to the making of a successful badminton athlete, by using a multidimensional approach. This multidimensional approach is inclusive of anthropometric, physical performance, motor coordination, psychological, cognitive characteristics, as well as coach`s views, knowledge and contribution to the sport of badminton. The following is a synopsis of the chosen pathway.In the first study (chapter 1), we provide a comprehensive analysis of a coach`s perspective on talent identification as it relates to anthropometric, physical performance and motor coordination characteristics. A comparison of views was done by coaches from three of the most popular racquet sports in the world (table tennis, tennis and badminton). A total of 177 coaches from around the world at different levels of expertise, shared their views via an online survey where they used a rating scale from 1 (lowest) to 10 (highest). They rated their suggestions and indicated what characteristics they felt were most important for their sport, based on exercises that were part of a generic test battery. In the end, coaches were proven to be knowledgeable about the components required for their discipline as key differences and similarities were identified. This research was helpful in showing that there is importance and value in testing of skill components and such information can assist coaches in future TID processes.In the second study (chapter 2), the focus shifted to identification of benchmarks for talent identification amongst a male youth badminton population. Sixty-one male participants between the ages of 12-18 were divided into different expertise groups (elite, sub-elite and novice). They were asked to execute a battery of exercises that was taken from a generic test battery consisting of: anthropometric, physical performance, motor coordination and also psychological characteristics (PCDEQ2). The inclusion of psychological factors was an important addition to the test battery, as that is often overlooked in such tests. In our statistical analysis, we also took into consideration measures to estimate biological maturity. From this data, we learned that there were significant differences between groups for physical performance characteristics (explosive power, flexibility, speed and endurance), BMI and motor coordination. The discriminant analysis reported 100% of correctly classified participants and 80% were correctly cross validated. This study was instrumental in highlighting data for the gaps that exist in literature pertaining to youth badminton profiles, and also showed that TID can also be achieved by using a generic testing tool.In the third and fourth studies (chapter 3 & chapter 4) we made significant strides by advancing our research into a more badminton specific category. Here we were more interested in learning more about the perceptuomotor (visual anticipation and decision-making) aspect of the sport of badminton. In particular for the third study, we explored the use of contextual information of badminton shots in different expertise levels. Fifty-eight participants were divided into elites, competitive players and novices. We assessed reaction time and anticipation accuracy by the use of badminton specific video-based occlusion tests. Within this, two conditions were created: (1) where only kinematic information was available showing only the last strokes, (LS) and (2) where both kinematic and contextual information was available, showing the full rallies (FR). Results showed that participants had slower reaction times in the FR condition with no differences in accuracy observed between the two conditions. The elite group was further sub-divided into groups of (adult elites, adult sub-elites & young elites). From this we learned that the adult elites proved to be faster at responding in the LS and FR conditions, when compared to the other elite groups. These particular results proved that even at the highest level of performers, anticipation performance can be discriminated between groups.In the fourth study, we continued with our investigations on anticipation. This time we wanted to dig a little deeper to find out what the differences were in expertise levels for anticipatory skill between badminton `in game` strokes (LS) and serves. We examined 58 participants usinglab based video occlusion design. Here we discovered that elite athletes were faster and more accurate in the LS condition than they were in the serves condition. This data can be used to assist coaches and athletes alike in improving their anticipatory skills, which are important in the sport of badminton. This research was also unique in that very rarely are two types of strokes analysed in one study as it pertains to badminton and visual anticipation, and the study was made to resemble as closely as possible real playing conditions for the participants.Our findings and insights are brought together in the general discussion where we also included a case study consisting of information from the analysis of a small dataset consisting of seven elite youth badminton players and a reference population consisting of 372 participants. Both groups consisted of boys and girls between the ages of 12-16 and the reference group was composed of persons who were non-athletes or performed some sort of physical activity or participated in sports other than badminton. We used a generic test battery (anthropometry, physical performance & motor coordination) but also included psychological (PCDEQ2 questionnaire) and cognitive (executive functions) characteristics. In this investigation, we wanted to find out what were the individual strengths of the elites. Based on this information, we wanted to find out if their strengths overshadow their weaknesses enough to make coaches select them nonetheless giving validation to the compensation phenomenon in sports. Overall, elite athletes fit the right description with their anthropometric measurements, and excelled in the physical performance, motor coordination and psychological characteristics with average cognitive performances when compared to the reference population.Based on all of our findings, we believe that we were capable of filling some notable gaps in the existing literature in the field of TID in badminton. We have demonstrated the importance of the coach`s knowledge to the sport and saw that their perspectives were later validated in our study on the youth elite. Our research on anticipation and decision-making produced a research design that was different to most of the studies available and the results show exciting and new information.This information can make significant new contributions for badminton aficionados of all backgrounds who are interested in improving their performance standards. Our data on the seven elites, provides further insight into the methods and details that badminton coaches utilise in their selection processes, and how important their input is for the longevity of the athlete and production of successful performance results. For future research, we recommend that more badminton specific talent test batteries be formulated and implemented for TID, and innovative ways be developed to help train anticipation and decision-making skills.